Ethics of Prudential Insurance Agents in Marketing Life Insurance Products - Anjali Marwiyah Siregar; Yusrizal Yusrizal (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study is to find out how the ethics of Prudential insurance agents in marketing life insurance products at PT. Prudential Life Assurance Binjai Branch. The type of research used is descriptive using a qualitative approach. Based on the results of research and analysis that has been carried out, it can be seen that the ethics of the insurance agent Prudential Binjai branch in marketing the product there is no special training from the company about sharia insurance, but the agents are given several requirements and strengthened by the agent code of ethics from Prudential in the form of a guide book. Life insurance product marketing strategy at PT. The Prudential Life Assurance of the Binjai Branch according to Islamic economics has not been running well in accordance with the principles of Islamic Economics because there have been several violations, ranging from agency recruitment to the system that the company pays little attention to.